Towards a link between Instructional Approaches and Gamification - A Case Study in a Programming Course - Silva, Fernando; Toda, Armando; Isotani, Seiji (Anais do Workshop de Informática na Escola (WIE), 2018)
Students' motivation play an important role in their educational process. Several studies indicate that the lack of motivation hinders students' learning. To mitigate this problem researchers have been using Gamification to solve engagement and motivational problems, which aroused the interest of teachers and instructors. However, those education professionals does not have time, resources nor knowledge on how to apply those game concepts within their learning environments. Based on this premise this work present an approach to support planning, development and evaluation of gamification, supported by instructional technologies, in order to improve students motivation. We used an ontology-based tool called SMARTIES and a gamification generic framework (6D) and carried out a case study with twelve students in an introductory computer science course for pre-service teachers. We were able to create gamified strategies using this approach. Secondly, we applied those strategies within four classes of the course. Our results demonstrate that our gamified strategies increased students motivation, interest and perceived competence through the case study. We concluded that gamification can achieve positive results when tied to instructional objectives and through the use of a systematic approach to support the planning process.